OCD - Tools to Help Young People Fight Back! : a CBT Manual for Therapists. - Turner, Cynthia (Jessica Kingsley Publishers, 2019)
This practical and accessible manual outlines a 14-session programme with which to treat young people affected by OCD using cognitive behavioural therapy. Designed to be used alongside a complementary workbook, it offers practical guidance on how to treat young people, educate both patients and their families and facilitate recovery.